Deciphering complex groundwater age distributions and recharge processes in a tropical and fractured volcanic multi‐aquifer system. Issue 3 (27th February 2022) - Sánchez‐Murillo, Ricardo; Montero‐Rodríguez, Irene; Corrales‐Salazar, José; Esquivel‐Hernández, Germain; Castro‐Chacón, Laura; Rojas‐Jiménez, Luis D.; Vargas‐Víquez, José; Pérez‐Quezadas, Juan; Gazel, Esteban; Boll, Jan
Abstract: Groundwater recharge in highly fractured volcanic aquifers in the humid tropics remains poorly understood. In this region, rapid demographic growth and unregulated land use change are resulting in extensive surface water pollution and a large dependency on groundwater extraction. Here we present a multi‐tracer approach including δ 18 Oδ 2 H, 3 H/ 3 He dating, and noble gases (NG) within the most prominent multi‐aquifer system of central Costa Rica, with the objective to assess dominant groundwater recharge mechanisms and age distributions. We sampled wells and large springs across an elevation gradient from 868 to 2421 m asl. Our results indicate relatively young apparent ages ranging from 0.0 ± 3.2 up to 43.5 ± 7.6 years within the unconfined aquifer system. Helium isotopes (R/Ra up to 5.4) indicate a dominant signal from the upper mantle and preclude 3 H/ 3 He dating in 50% of the samples. Potential recharge elevations (based on NG and δ 18 O) ranged from ~1350 to 2670 m asl. NG‐derived recharge temperatures ranged from 11.0°C to 19.4°C. Recharge estimates varied from 129 ± 78 to 1605 ± 196 mm/yr with a mean value of 642 ± 117 mm/yr, representing 20.1 ± 4.0% of the total mean annual rainfall as effective recharge. The shallow unconfined aquifer is characterized by young and rapidly infiltrating water, whereas the deeper aquifer units have relatively older water (>60 years). These results are intended to guide the delineation and mapping of critical recharge areas in mountain headwaters to enhance water security and sustainability in the most important headwater dependent systems of Costa Rica. Abstract : The unconfined aquifer unit is characterized by young groundwater (0.0 ± 3.2 up to 43.5 ± 7.6 years), rapid percolation, and a high susceptibility of contaminant transport (i.e., residential untreated wastewater). The semi‐confined aquifer units are characterized by older (>60 yr) groundwater. Apparent age separation within the multi‐layer aquifer was further confirmed by the spatial trends in δ 18 O and tritium activity. Helium isotopes (R/Ra up to 5.4) indicate a dominant signal from the upper mantle and preclude 3 H/ 3 He dating in 50% of the samples.